Pengaruh Ketidakseimbangan Beban Terhadap Efesiensi Transformator Distribusi Studi Gardu PT PLN (PERSERO) Area Bekasi - Rio Afrianda; Samsurizal Samsurizal; Afifah Annisa Nurul (Sutet, 2020)
Load unbalance in an electric power system often occur to meet consumer needs. Distribution of the load that was initially evenly will experience an unbalance when the burdens. As a result, current arises in the transformer neutral, current flowing in the transformer neutral causes losses, losses in the neutral conductor transformer and current flowing to the ground. Technically, if these losses occur continuously, it will be detrimental to PLN and can reduce transformer efficiency. For the supply of electricity to remain stable and continuity, it must be overcome